Предмет: Алгебра,
автор: menhuka2675
Решите уравнение х(х^2 + 6х +9) = -2(x+3).
Ответы
Автор ответа:
0
Ответ:
разделим левую и правую часть на х+3
Также уравнение будет равно нулю, когда х²+6х+9 и -2(х+3)=0
-2(х+3)=0
-2х-6=0
-2х=6
х= -3
х²+6х+9=0
(х+3)²=0
х= -3
Ответ: -3; -2; -1
Автор ответа:
0
Ответ:вот
Объяснение:
Приложения:
Похожие вопросы
Предмет: Русский язык,
автор: Diko20051
Предмет: Русский язык,
автор: Deniska2202
Предмет: Русский язык,
автор: ValentinGontar
Предмет: Русский язык,
автор: KyTaKbaLLI
Предмет: Физика,
автор: markburmistrovp8f31z